THU0347 Impact of obesity on the response to tumour necrosis factor inhibitors in axial spondyloarthritis. (15th June 2017) - Micheroli, R; Hebeisen, M; Scherrer, A; Wildi, L; Exer, P; Tamborrini, G; Bernhard, J; Möller, B; Zufferey, P; Nissen, MJ; Ciurea, A
Abstract : Background: Few studies have investigated the impact of obesity on response to tumour necrosis factor inhibitors (TNFi) in patients with axial spondyloarthritis (axSpA). Objectives: To investigate the impact of different Body Mass Index (BMI) categories on TNFi response in a large cohort of patients with axSpA. Methods: Patients within the Swiss Clinical Quality Management cohort were included if they fulfilled the ASAS criteria for axSpA, started a first TNFi after recruitement and had available BMI data as well as a baseline and follow-up visit at 1 year (±6mo) (N=632). Patients were categorized according to BMI: normal (BMI 18.5 to <25), overweight (BMI 25 to 30) and obese (BMI >30). We evaluated the proportion of patients achieving the 40% improvement ASAS criteria (ASAS40) as well as Ankylosing Spondylitis Disease Activity Score (ASDAS) improvement and status scores at 1 year. Patients having discontinued the TNFi were considered non-responders. We controlled for age, sex, HLA-B27, axSpA-type, BASDAI, BASMI, elevated CRP, current smoking and physical exercise in multiple adjusted logistic regression analyses. Results: In comparison to normal weight and overweight patients, obese individuals were significantly older, had a longer symptom duration and higher BASFI and BASMI levels, while ASDAS levels were comparable between the 3 groups (Table 1 ). Data to calculate the ASAS40 response was available in 496 patients (78%). It was reached by 44%, 35% and 28% of patients with normal weight, overweight and obesity, respectively, (p=0.02; Table 2 ). A significantly lower odds ratio (OR) for achieving ASAS40 response was found in adjusted analyses in obese patients vs patients with normal BMI (OR 0.30, 95% confidence interval (CI) 0.11–0.73, p=0.01). Comparable results were found for the other outcomes assessed. The respective adjusted ASAS40 OR in overweight vs. normal weight patients was 0.69, 95% CI 0.38–1.24, p=0.22. Conclusions: Obesity is associated with significantly lower response rates to TNFi in patients with axSpA. Disclosure of Interest: None declared